Fabrication and characterization of tissue engineering scaffold with controllable porosity and interconnectivity - Ng, Chek Lee. (2010)
One of the key issues in fabricating tissue engineering scaffold is to have control over the structural properties. This study explored the fabrication techniques of tissue engineering scaffold which allows control over the scaffold porosity and interconnectivity. For simplicity’s sake, scaffolds with uniform pore size were fabricated. Mono-dispersed polymethyl methacrylate and polystyrene microspheres were used as porogen. Polymer microspheres were fabricated using the emulsion-solvent evaporation method. Microsphere templates with highly ordered packing were obtained using ultrasonic vibration. Investigation was carried out to understand the sintering behavior of the polystyrene microspheres and was found to be consistent with Frenkel’s model, which suggests viscous flow as the main sintering mechanism. Gelatin scaffolds encompassing microsphere templates were dried via the freeze drying process, followed by cross-linking of gelatin using heat. The microsphere templates within the scaffolds were removed by dissolution in dioxane, followed by displacing the dioxane with ethanol. The scaffolds were dried using the critical point drying technique. Theoretical models describing scaffold porosity and interconnectivity were derived by establishing the relationship of these parameters in terms of the neck length of sintered microspheres. Observations showing no particle deformation other than the necking region, combined with the occurrence of microsphere template densification verified the assumption made in the models. By understanding the sintering behavior and utilizing the theoretical models, the porosity and interconnectivity of scaffold can be predicted or controlled.